2021
DOI: 10.3389/fncom.2021.698386
|View full text |Cite
|
Sign up to set email alerts
|

Functional Brain Networks in Mild Cognitive Impairment Based on Resting Electroencephalography Signals

Abstract: The oscillatory patterns of electroencephalography (EEG), during resting states, are informative and helpful in understanding the functional states of brain network and their contribution to behavioral performances. The aim of this study is to characterize the functional brain network alterations in patients with amnestic mild cognitive impairment (aMCI). To this end, rsEEG signals were recorded before and after a cognitive task. Functional connectivity metrics were calculated using debiased weighted phase lag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 62 publications
(96 reference statements)
2
18
0
Order By: Relevance
“…We also found no significant pre-to-post differences in these two measures over the whole cohort or between groups. This endorses the idea that MST parameters are more sensitive to detect profound changes in brain networks for MCI patients than conventional measures ( López et al, 2017 ; Požar et al, 2020 ; Youssef et al, 2021 ).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We also found no significant pre-to-post differences in these two measures over the whole cohort or between groups. This endorses the idea that MST parameters are more sensitive to detect profound changes in brain networks for MCI patients than conventional measures ( López et al, 2017 ; Požar et al, 2020 ; Youssef et al, 2021 ).…”
Section: Discussionsupporting
confidence: 76%
“…If we compare trees A and B in Figure 1 , then A is more integrated than B and both the leaf number and tree hierarchy are higher in A than in B. In contrast, if we compare trees B and C in Figure 1 , then B is more integrated than C, but the leaf number is the same in both trees while the tree hierarchy is smaller in B than in C. Hence, we cannot immediately conclude that increased MST hierarchy reported in Youssef et al, (2021) indicates a more integrated topology. However, in the same study one can find that the percentage of change in mean beta leaf number was not preserved from the pre- to post-task timepoint but was slightly decreased in the control group and slightly increased in the aMCI group.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Several studies have demonstrated the utility of these features in the analysis of EEG signals. For instance, they have been used in brain-computer interface (BCI) control and EEG-controlled robotic navigation, 54 as well as in the assessment of mild cognitive impairment, 44,55 attention deficit hyperactivity disorder, 56 neurodegenerative disorders such as Alzheimer's disease, 26 and extraction of information from different biomedical signals. [57][58][59] We also observed a decline in cognitive function 6-12 months after acute COVID-19 infection, as demonstrated by TMT-A.…”
Section: Discussionmentioning
confidence: 99%